Constituintes químicos de Erythrina velutina Willd.(FABACEAE) - Cabral, Analucia Guedes Silveira (2009)
The family Combretaceae comprises of genera with over 600 species, in which Combretum and Terminalia are the two largest genera, with about 250 species each. Aiming to contribute to the chemotaxonomic study of the family Combretaceae and the genus Combretum, the leaves of Combretum duarteanum were subjected to phytochemical and pharmacological study. The essential oil (2.0 mL) was obtained from fresh leaves by steam distillation of the species, and subsequently analyzed by Gas Chromatography coupled to Massass Spectrometry. The extracts and phases obtained were subjected to usual chromatographic methods for the isolation and purification of the chemical constituents. For the identification of the isolated substances, spectroscopic methods such as infrared, uni-dimensional and bidimensional spectroscopic 1H NMR and 13C NMR for mass spectrometry were used in addition to the comparison with published data. Chemical studies of the C. duarteanum leaves resulted in the identification of twelve substances: cycloartane- 24-ene-1α, 3β-diol (Cd-1), isolated for the first time in the investigated family; 2α, 3β- urs-12-en-28-oic acid (Cd-2); 4α-carboxy-3β-hydroxy-24-cycloartenol (Cd-3), isolated for the first time in the genus Combretum; 2α, 3β, 28-trihidroxiurs-12-ene (Cd-4); 2α, 3β acid, 23α-trihidroxiurs-12-ene-28-oic acid and 2α, 3β, 23α-trihydroxyolean-12-ene- 28-oic acid (Cd-5); stigmasterol (Cd-6); stigmasterol and spinasterol (Cd-7); methyl gallate (Cd-8); 3',5,7-trihydroxy-3, 4'- dimethoxyflavone (Cd-9); 5,7,3',4'- tetrahydroxyflavone-3-O-galactopyranoside (Cd-10), catechin (Cd-11) and kaempferol-3-O-β-D-glucopyranoside (Cd-12). The chemical composition of the essential oil showed twenty-eight components, among which spathulenol (15.1%) and β-caryophyllene (14.1%) were the major compounds. Hexane, chloroform, ethyl acetate, methanol extract phases, as well as the Cd-2, Cd-5, and CD-10 substances were tested against bacterial strains of Gram positive and Gram negative, strains of the Candida genera. All phases, extracts and substances tested did not show any significant antibacterial and antifungal activity. Substances Cd-2, Cd-5, Cd-9 and Cd- 10 were tested in vitro during the cytotoxicity assay on Ehrlich ascites carcinoma cells, in order to evaluate antitumor activity. The substances Cd-2 (IC50 = 17.82 μg/mL) and Cd-5 Cd-2 (IC50 = 31.23 μg/mL) showed potent cytotoxic activity.